2009
DOI: 10.1371/journal.pbio.1000057
|View full text |Cite
|
Sign up to set email alerts
|

Cargo and Dynamin Regulate Clathrin-Coated Pit Maturation

Abstract: Total internal reflection fluorescence microscopy (TIR-FM) has become a powerful tool for studying clathrin-mediated endocytosis. However, due to difficulties in tracking and quantifying their heterogeneous dynamic behavior, detailed analyses have been restricted to a limited number of selected clathrin-coated pits (CCPs). To identify intermediates in the formation of clathrin-coated vesicles and factors that regulate progression through these stages, we used particle-tracking software and statistical methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

61
647
7
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(719 citation statements)
references
References 35 publications
61
647
7
4
Order By: Relevance
“…This was similar to previous estimates in BSC1 cells, wherein productive CCSs were defined as spot-like CCSs having lifetimes anywhere from tens to hundreds of seconds (average 87 s) [3,27,28]. Because the size and lifetimes of scission-detected CCSs were so variable ( Figure 1H and 1I), in our subsequent investigation of late events in CME we made measurements over a time window of 680 s, centred on scission.…”
Section: Author Summarysupporting
confidence: 81%
See 2 more Smart Citations
“…This was similar to previous estimates in BSC1 cells, wherein productive CCSs were defined as spot-like CCSs having lifetimes anywhere from tens to hundreds of seconds (average 87 s) [3,27,28]. Because the size and lifetimes of scission-detected CCSs were so variable ( Figure 1H and 1I), in our subsequent investigation of late events in CME we made measurements over a time window of 680 s, centred on scission.…”
Section: Author Summarysupporting
confidence: 81%
“…Therefore, scission events defined a class of larger, longer-lived CCSs. The shorter-lived scission-undetected CCSs most likely correspond to the ''abortive'' CCSs described previously [3,27,28], although some of these structures may have represented endosomal clathrin.…”
Section: Author Summarymentioning
confidence: 59%
See 1 more Smart Citation
“…S5 A-N). With respect to DYNAMIN, which is known to complete vesicle formation through membrane fission (44), previous studies have shown it is also present and functionally important at early stages of CLATHRIN-mediated endocytosis (45,46). AZ localization of endocytic proteins might suggest a mechanism of release site clearance involving rapid formation of CLATHRIN-coated vesicles directly from the AZ; however, this mechanism is not favored, primarily because ultrastructural studies indicate that CLATHRIN-coated vesicles form at PAZ, rather than AZ, regions of the plasma membrane (47,48) (Fig.…”
Section: Rapid Endocytic Mechanisms Maintaining Neurotransmitter Releasementioning
confidence: 99%
“…L'initiation de la formation de vésicu-les de clathrine est une étape difficile à étudier : les puits recouverts de clathrine se forment et deviennent des vésicules relativement rapidement (20 à 90 secondes), sont trop petits (environ 100 nm) pour être observés directement par microscopie optique et se forment aléatoirement sur la surface des cellules [19,20]. L'adaptateur AP2 a longtemps été considéré comme responsable de la nucléation des puits de clathrine.…”
Section: Induction Des Vésicules De Clathrine : Le Rôle Controversé Dunclassified